1959
DOI: 10.1136/hrt.21.3.343
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Changes in the Electrocardiogram in Hypothermia

Abstract: Death from ventricular fibrillation is the gravest risk that attends the current use of hypothermia in surgery of the heart and brain. Any reliable warning of its approach would clearly be important.In 1938 Tomaszewski published electrocardiograms from an accidentally frozen patient that showed an extra, slowly inscribed deflection between the QRS complex and the early part of the S-T segment. This deflection was produced experimentally in dogs in 1943 by Grosse-Brockhoff and Schoedel, and has been described b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

1962
1962
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…7,24 However, subsequent studies found no correlation between the time of onset or prominence of the deflection and the onset of ventricular fibrillation. 15 In a report of 47 anesthetized dogs, an increase in amplitude of the so-called ''characteristic slowly-inscribed inflection'' occurred as the temperature fell. 15 The degree of prolongation of the PR, QRS, and ST segments bore no relation to prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7,24 However, subsequent studies found no correlation between the time of onset or prominence of the deflection and the onset of ventricular fibrillation. 15 In a report of 47 anesthetized dogs, an increase in amplitude of the so-called ''characteristic slowly-inscribed inflection'' occurred as the temperature fell. 15 The degree of prolongation of the PR, QRS, and ST segments bore no relation to prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a report of 47 anesthetized dogs, an increase in amplitude of the so-called ''characteristic slowly-inscribed inflection'' occurred as the temperature fell. 15 The degree of prolongation of the PR, QRS, and ST segments bore no relation to prognosis. 17 Because the current of injury decreased with increasing the respiratory minute volume or decreasing the concentration of bicarbonate, it was postulated that the ECG change was not directly associated with low temperature but with acidemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations